Plasma Processing of B4C–TiB2 Eutectic Composite Powders. Issue 7 (17th June 2013) - White, Ryan M.; Kunkle, Jamie M.; Haines, Chris; Dickey, Elizabeth C.; Fahrenholt, W. G.
<x xml:space="preserve">Abstract</x> The production of a composite powder of eutectic B4C–TiB2 is demonstrated via an atmospheric plasma processing method. Feedstock material is prepared for plasma processing by mixing and spray drying monolithic B4C and TiB2 to produce a flowable precursor powder. These powders are fed through a plasma torch, where they are melted and actively quenched in flight with argon gas. Plasma processed powders are composed of crystalline B4C and TiB2, with some additional B2O3 oxide phase. The plasma processing method results in the production of monolithic B4C and TiB2 nanoparticles, but some larger particles (generally ≥10 μm in diameter) are shown to contain the traditional lamellar eutectic microstructure. The eutectic interphase spacing ranges from 100 to 650 nm, and the composite microstructure is present through the entire thickness of the eutectic particles. Future work on plasma processing of eutectic powders should focus on methods utilizing passive in‐flight quenching to increase the average particle size.